الأثر الفلسفي في توظيف الزمن الصيغي عند النحاة - خضير, حسين علي (Journal of College of Education, 2018)
The concept of time and its relation to movement and change has been taken into account by philosophers. They see that time is synonymous with movement, the universe and corruption; hence the sacred self being excluded from entry into time; They represent the everlasting eternity and the eternal permanence, which are beyond time and its three dimensions: "past, present and future".                                                                                We note from this philosophical correlation what refers to the philosophical dimensions of the time of the past, the present and the future, including the presence and movement corresponding to occurrence and renewal and continuity and permanence and other terms, which is useful to link them with the linguistic theories that build upon them; In the definition of the semantics of acts and the work of the descriptions or the so-called semi-act descriptive derivatives, for example, and is linked to the three indications: "Iddih, and temporal, and self" each, which is expressed by Ibn Jnei (d. 392 e) by the word "lexicon" Industrial "job Of "moral" Allazmih ". It is a mature subject of study in the light of semantic research within a wide level of language levels.                                                                                         Based on this movement of human existence and its relation to the movement of linguistic presence, Arabic is undoubtedly the language of time; its ability to express and clarify words that have absorbed time accurately, in all its dimensions and trends, "proximity, distance, continuity, communication and interruption". Is clear in the use of those temporal signs at the level of form and context, and it has been time, and absorbed all the reach of human thought and the reach of the march of life.If we know that time represents the movement, we know the extent of its relation to the movement of human existence. This shows the interest of the grammarians in the movement of the verb and its temporal significance in constructing the context of the sentence, because it represents the shining face of the language, and that "acts are the movement of the actors" Event Movement.